2001
DOI: 10.1002/hyp.277
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and isotopic methods for confirming the roles of wadis in regional groundwater recharge in a regional arid environment: a case study in Al Ain, UAE

Abstract: Abstract:In arid environments groundwater may represent the most important source of water for sustaining life. The timing and nature of precipitation may induce infiltration and recharge on a small scale. The Al Ain region, UAE was chosen and from 1996 to 1997 studies were conducted to illustrate spatial distribution of recharge for groundwater by using chemical and isotopic methods. According to the field survey, UAE can be hydrogeologically classified into five parts: mountain area, wadis, sand dunes, inlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Lloyd, 1986;Gee and Hillel, 1988;Parissopoulos and Wheater, 1992;Tang et al, 2001). Because of the difficulty of monitoring flash flood events and of the large uncertainty in measuring recharge, modelling approaches appear to be an alternative to estimate groundwater recharge generated by seepage in the stream bed.…”
Section: Introductionmentioning
confidence: 99%
“…Lloyd, 1986;Gee and Hillel, 1988;Parissopoulos and Wheater, 1992;Tang et al, 2001). Because of the difficulty of monitoring flash flood events and of the large uncertainty in measuring recharge, modelling approaches appear to be an alternative to estimate groundwater recharge generated by seepage in the stream bed.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical and isotopic tracers have confirmed that ephemeral streams are cumulatively important areas for floodwaters to recharge groundwater aquifers in desert regions (Tang et al. ). In a synthesis of research into groundwater recharge in the Southwestern and Western U.S., Phillips et al.…”
Section: Connectivity Of Southwestern Ephemeral and Intermittent Streamsmentioning
confidence: 97%
“…If restricting soil or geologic layers underlying the channel do not substantially inhibit downward motion, channel transmission losses will recharge either the regional or alluvial groundwater (Tang et al. ; Constantz et al. ; Harrington et al.…”
Section: Connectivity Of Southwestern Ephemeral and Intermittent Streamsmentioning
confidence: 99%
“…Retaining spatio-temporal variations in hydrogen and oxygen isotopes in precipitation and groundwater, in conjunction with hydrologic observations and hydrochemistry, has been widely used to identify origins of water bodies (Vrbka et al 1993;Lambs 2000), infiltration modes of precipitation (Douglas 1997;Gazis and Feng 2004;Li et al 2007), the interactions between groundwater and other waters (Simpson and Herczeg 1991;McDonnell et al 1991;Mook 2000;Lamontagne et al 2005;Song et al 2006) and groundwater recharge mechanisms (Clark and Fritz 1997;Tang et al 2001;McGuire et al 2002;Rademacher et al 2003;Demlie et al 2007;Gates et al 2008). Limited isotopic studies have been performed in the Loess Plateau, mainly at profile or point scales.…”
Section: Introductionmentioning
confidence: 99%